Evaluación de los Sistemas Productivos de la Comunidad de Yugsiloma en Base al Mesmis, en la Provincia de Cotopaxi Cantón Latacunga, periodo 2018-2019 - Toapanta Panchi, Viviana Lucia (2019)
Yugsiloma community, in Juan Montalvo parish, is composed of minor and middle producers that are dedicated to the agricultural and industrial field whose economy consists of three activities that are: livestock, agriculture and bakery. The objective of this research was to evaluate the production systems in Yugsiloma community based on the MESMIS (Framework for Evaluation of Management Systems Incorporating Sustainability Indicators). Participatory indicators were established agricultural, economic, social and environmental, which allowed to measure the sustainability of the community in a certain period of time, before the intervention of the project and after it. Concerning the procedure carried out, a participatory diagnosis was developed with the association of women from Yugsiloma community (10 women), where 19 sustainability indicators were selected. These indicators were measured before and after the intervention carried out, in the 10 production units. In view of the results, it can be seen that the sustainability of the system, as a whole, has increased from 67.43% to 76.07, which is considered as a medium-high range of sustainability. This increase in values may be due to the fact that there has been a greater participation in training, which implies that they are now able to make their own organic fertilizers, and have a greater environmental awareness, which is reflected in the increase in the diversity of crops such as of livestock, in addition there is a slight improvement in the socioeconomic indicators. For example, in the industrial sphere they have more marketing points to sell their products derived from quinoa, although the indicators measured to analyze the empowerment of women in the community show that actions must still be taken to improve this process.